The performance of asynchronous transfer mode (ATM) in telecommunication system / Azman Mohd Isa - Mohd Isa, Azman (2006)
The performance of ATM in telecommunication system is the project to identify the ATM model network layer and ATM cell structure in telecommunication system network such as Telekom Malaysia Berhad ™. Also involved to know the ATM connection types until customer end. Thus, this project also evaluated so that we can discovered how better the performance ATM in actual live. The Network backbone coverage are peninsular Malaysia and East Malaysia ( Sabah & Sarawak) which is involved in various city such as Kuala Lumpur, Ipoh, Johore Baharu, Komtar, TTDI, Shah Alam ,Klang and others. Since communication such as Asynchronous Transfer Mode (ATM) networks play a vital role, an application's performance depends heavily on the quality of service provider like TM Berhad. In ATM network operation center, we heard complaints about network down due to trunk network connected to ATM equipment node. The Node located are at selected TM Exchange in Malaysia. To assure high performance on the ATM network, on analysis on overall performance should be done. It is important for ATM operation unit/group work together to achieve Total Customer Satisfaction. This research provides real measurement from ATM TM Berhad network operation center. The analysis clearly shows that the performance of A TM and the analysis of the ATM problems. This paper also proposes some suggestion and recommendation in order to have better performance in the future.